Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Given the function [tex]f(x) = x^3 - 6x^2 + 6x + 5[/tex], solve for [tex]f(x)[/tex].

Sagot :

To solve for [tex]\( f(5) \)[/tex] given the function [tex]\( f(x) = x^3 - 6x^2 + 6x + 5 \)[/tex], we need to substitute [tex]\( x = 5 \)[/tex] into the function and simplify step by step:

1. Substitute [tex]\( x = 5 \)[/tex] into the function:
[tex]\[ f(5) = 5^3 - 6 \cdot 5^2 + 6 \cdot 5 + 5 \][/tex]

2. Calculate [tex]\( 5^3 \)[/tex]:
[tex]\[ 5^3 = 125 \][/tex]

3. Calculate [tex]\( 6 \cdot 5^2 \)[/tex]:
[tex]\[ 6 \cdot 5^2 = 6 \cdot (5 \cdot 5) = 6 \cdot 25 = 150 \][/tex]

4. Calculate [tex]\( 6 \cdot 5 \)[/tex]:
[tex]\[ 6 \cdot 5 = 30 \][/tex]

5. Substitute these values back into the function:
[tex]\[ f(5) = 125 - 150 + 30 + 5 \][/tex]

6. Simplify the expression by performing the addition and subtraction in order:
[tex]\[ 125 - 150 = -25 \][/tex]
[tex]\[ -25 + 30 = 5 \][/tex]
[tex]\[ 5 + 5 = 10 \][/tex]

Therefore, [tex]\( f(5) = 10 \)[/tex].